2017
DOI: 10.1111/acer.13491
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of Alcohol Use Disorder and Chronic Pain: Genetic Influences on Brain Reward and Stress Systems

Abstract: Alcohol use disorder (AUD) is highly comorbid with chronic pain (CP). Evidence has suggested that neuroadaptive processes characterized by reward deficit and stress surfeit are involved in the development of AUD and pain chronification. Neurological data suggest that shared genetic architecture associated with the reward and stress systems may contribute to the comorbidity of AUD and CP. This monograph first delineates the prevailing theories of the development of AUD and pain chronification focusing on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 187 publications
1
13
1
3
Order By: Relevance
“…Twin studies indicate that up to half of the variability in both AUD and chronic pain may be explained by genetic factors, indicating a large genetic component for both conditions. A comprehensive review of genome‐wide association studies (GWAS) and candidate gene association studies (CGAS) that may explain the comorbidity between AUD and chronic pain was recently published (Yeung et al, ). The review specifically highlighted genes related to dysregulation of reward and stress systems (e.g., TBX19 ), genes involved in modulating reward and stress systems (e.g., ADRA1A, HTR7 ), and those genes that have involvement in the CNS, more broadly (e.g., CDH13 ).…”
Section: Comorbidity Of Problematic Alcohol Use and Painmentioning
confidence: 99%
See 2 more Smart Citations
“…Twin studies indicate that up to half of the variability in both AUD and chronic pain may be explained by genetic factors, indicating a large genetic component for both conditions. A comprehensive review of genome‐wide association studies (GWAS) and candidate gene association studies (CGAS) that may explain the comorbidity between AUD and chronic pain was recently published (Yeung et al, ). The review specifically highlighted genes related to dysregulation of reward and stress systems (e.g., TBX19 ), genes involved in modulating reward and stress systems (e.g., ADRA1A, HTR7 ), and those genes that have involvement in the CNS, more broadly (e.g., CDH13 ).…”
Section: Comorbidity Of Problematic Alcohol Use and Painmentioning
confidence: 99%
“…To our knowledge, no studies have examined genetic variants associated with the comorbidity of AUD and chronic pain in human samples. Yet, a few recent studies have expanded on the prior review by Yeung and colleagues (). An examination of genetic contributions to postoperative pain control across 42 studies concluded AUD was associated with genetic polymorphisms involved with pain sensitivity (Elmallah et al, ).…”
Section: Comorbidity Of Problematic Alcohol Use and Painmentioning
confidence: 99%
See 1 more Smart Citation
“…The co‐occurrence of chronic pain and alcohol use disorder (AUD) is well documented and involves complex interactions between genetic and neurophysiological aspects . Several studies have revealed bidirectional effects of chronic pain and AUD, with increased or decreased alcohol drinking in individuals with different pain problems, and the development of chronic pain in patients with alcohol problems (reviewed in Zale et al).…”
Section: Introductionmentioning
confidence: 99%
“…Certain health behaviors, such as smoking and alcohol use, have also been associated with pain [3,6,22,47,48,49]. People may use these types of behaviors in an attempt to cope with pain, and furthermore, health problems tend to co-occur with these behaviors, demonstrating another avenue through which pain intensity and behaviors like smoking and drinking may be linked.…”
Section: Introductionmentioning
confidence: 99%